Peran Generasi Digital Natives Terhadap Generasi Digital Immigrants Dalam Mencegah Penyebaran Berita Hoax Melalui Whatsapp - Nofi Eriany Simanjuntak (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Digital media and technology can be used to make human life easier, including communication, work, entertainment and access to news. In 2024, the Indonesian Internet Service Providers Association (APJII) presented survey results showing that internet users in the 12-27 year age group were 34.40%, in the 28-43 year age group 30.62%, in the 44 age group -59 years is 18.98%, the age group 60-78 years is 6.58%. Where digital natives were born in an era of rapid technological development and digital immigrants were born before technological developments. The aim to be achieved in this research is to identify the role of the digital natives generation versus the digital immigrant generation in preventing the spread of hoax news via WhatsApp social media. This research uses a qualitative approach with phenomenological methods. So, researchers found five categories, namely first, the role of digital natives in preventing hoax news, second, the highest spread of hoax news on social media, third, hoax news via WhatsApp social media, fourth, the spread of hoax news by the digital immigrants generation and fifth, hoax literacy by generations of natives and immigrants.